2019
DOI: 10.3389/fneur.2019.00881
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged Perivascular Spaces and Cerebral Small Vessel Disease in Spontaneous Intracerebral Hemorrhage Patients

Abstract: Background: Cerebral small vessel disease (SVD) is associated with cognitive decline, depression, increased mortality, and disability in stroke patients. MRI-visible perivascular spaces (PVS) are a sensitive neuroimaging marker of SVD. We aimed to explore the risk factors and associations with other SVD markers of PVS in two topographical regions (in the basal ganglia [BG] and centrum semiovale [CS]) in a cohort of spontaneous intracerebral hemorrhage (ICH) patients. Method: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 52 publications
1
10
1
Order By: Relevance
“…Our findings concerning the relationship of BG-E P V S w i t h a g e , h y p e r t e n s i o n a n d W M H w e r e consistent across different populations including lacunar stroke (28), intracerebral hemorrhage (12), and cognitive impairment (29). Besides, the stronger association between lacunar stroke and EPVS in BG than that in CS was similar to previous studies (3,30,31).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our findings concerning the relationship of BG-E P V S w i t h a g e , h y p e r t e n s i o n a n d W M H w e r e consistent across different populations including lacunar stroke (28), intracerebral hemorrhage (12), and cognitive impairment (29). Besides, the stronger association between lacunar stroke and EPVS in BG than that in CS was similar to previous studies (3,30,31).…”
Section: Discussionsupporting
confidence: 88%
“…As EPVS scores were not normally distributed, we dichotomized EPVS into mild total EPVS (score 0-2) vs. moderate-tosevere total EPVS [3][4][5][6][7][8], mild BG-EPVS [0-1] vs. moderateto-severe BG-EPVS [2][3][4], and mild CS-EPVS [0-1] vs. moderate-to-severe CS-EPVS [2][3][4], respectively. Potential variables identified from the recent literature (11,12,27) were adjusted: age, sex, hypertension, diabetes mellitus, dyslipidemia, AF, prior stroke/TIA, smoking, drinking, lacunar stroke, PWMH, DWMH, and lacunes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underlying dilatation of PVS and the actual function of PVS have yet to be adequately clarified. Etiologies related to the enlargement of PVS include aging, hypertension, stroke, cerebral small vessel diseases including lacunar stroke and white matter hyperintensities, systemic inflammation, and multiple sclerosis [13] . Recent studies have shown that PVS are involved in the drainage of interstitial fluid, soluble waste proteins, and metabolic products, including Aβ protein, from the brain in cooperation with brain arteries and glial cells facilitated by aquaporin 4 water channels [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of the current study is two-fold. First, EPVS rating, specifically in the basal ganglia, has been shown to correlate strongly with other measures of CSVD, cognitive impairment at 1 year after ischemic stroke, and stroke risk factors in hemorrhagic stroke cohorts 5 , 6 . Additionally, previous studies have found that EPVS rating scores in the basal ganglia are commonly not normally distributed and have found that a meaningful categorization for logistic regression to be 10 punctate EPVS, where < 10 is considered none-to-mild and ≥ 10 is considered moderate-to-severe 7 .…”
Section: Introductionmentioning
confidence: 98%